Design principles for foundations on expansive soils - Chao, Kuo-Chieh, author; Nelson, John D., advisor; Overton, Daniel, advisor (Colorado State University. Libraries, 2007)
The design of foundations for sites having expansive soils is one of the greatest challenges facing geotechnical engineers today. Intolerable heave of foundations on expansive soils often affects critical safety aspects of structures. Therefore, it is imperative that design of foundations for expansive soils includes analyses of expected heave and consequences of foundation movement over the design life of the structure.

Current technology generally considers the amount of predicted heave that will ultimately occur at a site. Design of foundations for extreme ultimate conditions is not always practical and economical in engineering practice. When large values of heave are predicted, the depth of potential heave may be very deep, and the time required for the wetting front to reach large depths of potential heave may exceed the design life of the structure. In that case, it is important to consider the rate of water migration in the vadose zone. Thus, design of foundations for buildings on expansive soils must consider the migration of the subsurface water that will occur during the design life of the structure, and the amount of heave that such wetting will produce. Current design procedures that are in common use are deficient in this respect.

Appropriate design of foundations on expansive soils must consider accurate prediction of soil/bedrock heave and the effect of that heave on foundation movement can be modeled accurately, and that future consequential movement of the foundation system can be accurately predicted.

The hypothesis of this research is that analyses of the expected wetting of the subsoils, and the prediction of amount and nature of heave associated with that wetting, must be a critical part of the design and construction of foundations on expansive soils. In this way, the design methodology for foundations on expansive soils will be improved, and will optimize performance of all elements of the structure.

A major problem in developing the design principles for foundations on expansive soils is that comprehensive field data for a long period of time at a site are usually not available. One building that has been undergoing distress for approximately 15 years is the TRACON building at Denver International Airport, Denver, Colorado. This building is owned by the Federal Aviation Administration and is located on a site having highly expansive soils. Water migration and foundation movement at the TRACON building have been monitored intensely over the past six years. Extensive modeling of the field results has provided particularly useful insight into the behavior of the foundations, and has provided the basis for the development of the design principles for foundations on expansive soils that is presented in this dissertation.

The goal of this research is to advance the state of the art with respect to foundation design by developing a methodology to apply rigorous engineering principles in the design of foundations on expansive soils.

To accomplish the goal, the objectives of this research are: • to develop a means of installing stable survey benchmarks. • to develop an accurate methodology to analyze the migration of subsurface water in unsaturated expansive soils. This includes the investigation of the soil water characteristic curve for the expansive bedrock. • to develop a means of predicting timewise changes in heave based on measured survey data or computer modeling of the water migration. • to develop a rigorous and appropriate design methodology for foundations on expansive soils.

A water migration study was performed using the VADOSE/W models with the input parameters and boundary conditions calibrated over the period from May 2001 to June 2004 and validated over the period from July 2004 to August 2006 using observed subsurface nuclear gauge data. The results of the analyses have demonstrated that rigorous computer modeling can be performed to analyze the actual migration of subsurface water within the subsoils. Projection of subsurface water migration into the future until the end of the design life of the structure was then possible.

Using the relationship between water content and percent swell developed herein, along with computer modeling of the wetting of the subsoils, heave as a function of time can be predicted. The effects of climate and irrigation must be included in the modeling. The change of heave with time was also predicted by fitting the observed survey data to a hyperbolic equation. In doing so, it was necessary to take into account the maximum ultimate heave predicted using the heave equation.

A design methodology for foundations on expansive soils was proposed based on the field data collected at the TRACON site. This methodology considers the timewise pattern of migration of water within subsoils and the associated heave that such wetting will produce over the design life of a structure. The proposed design methodology was verified over a period of 5 years at the TRACON site. It is believed that the methodology can be applied over the design life of the structure.

The methodology was demonstrated for various design conditions by performing water migration analyses and rate of heave calculations on a hypothetical site. The results of the study indicate that, if the progression of heave over the design life of the structure is considered, the required pier length can be reduced significantly compared to that using the current design methodology. Furthermore, the effect of overexcavating and replacing the upper few meters of expansive soil in combination with installing piers is considered. In summary, the proposed design methodology provides a practical and economical approach to design foundations on expansive soils.
Keywords: expansive soils; foundations; water migration; civil engineering; environmental engineering